Possible Impossibilities of Peace Construction in ELT: Profiling the Field - Yeraldine Aldana-Gutiérrez (HOW, 2021)
When referring to peace, peacebuilding, and peace education, among others, some similarities and differences among them appear. Although some consider ELT as a peripheral field regarding peace construction, diverse enunciation modalities profile this interest. Inquiring into what, where, when and who, I analyzed 55 articles and 36 presentation abstracts for this qualitative study to unveil what is understood as peace construction in ELT. This revision presents six tendencies. Gaps and opportunities of research action for teachers are synthesized. Time/space coordinates of enunciation modalities in peace construction are displayed. I describe who the teachers behind some studies might be, regarding their locus of enunciation. Conclusion remarks around the diverse nature of peace construction are discussed, as representing those links between imagined separated fields.